Nanocrystalline Manganese Iron Oxide as a Charge Storage Electrode. Issue 9 (2nd June 2016) - Soni, Disha; Pal, Rahul
Abstract: Phase pure nanocrystalline manganese iron oxide [(Mn0.37 Fe0.63 )2 O3 ] was synthesized by combustion technique based on propellant chemistry principle employing citric acid as fuel. The synthesized powder was characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), BET, BJH analysis and electrochemical studies for possible application as a charge storage electrode. The average crystallite size was found to be 18.6 nm from XRD analysis. BET analysis yielded the surface area and specific pore volume of the powder to be 22.96 m 2 g −1 and 0.0098 cm 3 g −1 respectively. The specific capacitance from cyclic voltammetric studies at scan rate 5 mV s −1 was found to be about 30 F g −1 cm −2 while from charge discharge studies was found to be 27±1 F g −1 cm −2 . In addition, the material showed appreciable stability during charge‐discharge cycling. Abstract :